Feasibility study on the regeneration of spent activated carbon from oleochemical industry with microwave - Mazelan, Abdul Qahar (2019)
Regeneration of spent activated carbon through microwave regeneration offers some advantages over conventional treatment methods. The regeneration of spent activated carbon from oleochemical industry through microwave irradiation under different operating conditions has been investigated. The surface porosity and functional group for virgin, spent and regenerated activated carbons samples were characterized in the study. The adsorption uptake of the virgin and regenerated activated carbon was identified through batch adsorption experiment with methylene blue solution. Surface area of the activated carbon exhibit larger mesopore surface area than micropore surface area. Microprore surface did not appear when the spent activated carbon regenerated at power level below 1000 W and heating time below 9 min. Longer heating period are required to preserve the porosity and adsorption performance of the activated carbon in order to high regeneration efficiency